Topical erythropoietin as a novel preventive and therapeutic agent in bisphosphonate-related osteonecrosis of the jaw - Pantea Nazeman; Maryam Rezai Rad; Arash Khojasteh (Wolters Kluwer Medknow Publications, 2016)
Introduction: One of the most common side effects of bisphosphonate intake is osteonecrosis of the jaw (ONJ) which may develop following dentoalveolar interventions. Despite the vast available protocols, there is no clear guideline in the management of this condition. In osteonecrosis, the number and proliferation of bone-forming cells as well as vascularity are disturbed. Erythropoietin (EPO) is a hematopoietic hormone with angiogenic, osteogenic, and antiapoptotic properties. The Hypothesis: It is suggested to utilize poly lactic-co-glycolic acid hydrogel containing 1500-3000 IU/kg EPO following dentoalveolar surgery in samples receiving bisphosphonates as a preventive or therapeutic agent. Evaluation of the Hypothesis: Considering the pathophysiology of ONJ and therapeutic properties of EPO, it is assumed that EPO may be effective in treatment of ONJ. Furthermore, as a preventive measure, utilizing EPO following dentoalveolar surgery may be beneficial in the patients at risk of ONJ.